Physics of magnetic thin films : theory and simulation - Diep, H. T. (Singapore : Jenny Stanford Publishing, 2021)
This book is for graduate students and researchers who wish to understand theoretical mechanisms lying behind macroscopic properties of magnetic thin films. It provides a detailed description of basic theoretical methods and techniques of simulation to help readers in their research projects. The first part of the book contains 6 chapters. Chapters 1 to 5 focus on the fundamental theory of bulk magnetic materials. Chapter 6 is devoted to the presentation of the Monte Carlo simulation methods. Exercises and problems are provided at the end of each of these chapters for self-training. The second part contains 11 chapters devoted to the main topic of the book, namely physics of magnetic thin films: theory and simulation. Written as a research paper, each chapter focuses on a subject and also presents the state-of-the-art literature on the subject and the motivation of the chapter. A detailed description of the techniques and the presentation of the results are then shown with discussion.
Spin -- Origin of Magnetism. Mean-Field Theory of Magnetic Materials. Theory of Spin Waves. Green's Function Theory in Magnetism. Theory of Phase Transitions and Critical Phenomena. Monte Carlo Simulation: Principle and Implementation. Exactly Solved Frustrated Models in Two Dimensions. Spin-Wave Theory for Thin Films. Frustrated Thin Films of Antiferromagnetic FCC Lattice. Heisenberg Thin Films with Frustrated Surfaces. Phase Transition in Helimagnetic Thin Films. Helimagnetic Thin Films in a Field. Spin Waves in Systems with Dzyaloshinskii-Moriya Interaction. Skyrmions in Thin Films. Skyrmions in Superlattices. Thin Films and Criticality. Spin Resistivity in Thin Films. Solutions of Exercises and Problems.
OCLC-licensed vendor bibliographic record.
Keywords: Thin films -- Magnetic properties; Magnetic films; SCIENCE / Solid State Physics; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science